The Effect of Android-Based Learning Using Smart Apps Creator (SAC) on Students' Integrated Science Interest - Khotimah, Husnul; Nawir, Muhammad; Ayu, Sadriana (DIDAKTIKA, 2023)
Smart Apps Creator (SAC) enables teachers to develop android-based learning media without requiring coding expertise. Numerous studies have explored the development of SAC media. However, research specifically focused on the effect of SAC on students' interest in integrated science subjects remains severely limited. Therefore, this study aims to investigate the effect of SAC on students’ integrated science interest. This study involved 27 students on the second grade at SMPN 2 Bontomarannu, South Sulawesi. It employed an experimental approach with a pre-experiment method, utilizing a one-shot case study model. Data collection involved observation and questionnaires. The data were analyzed using descriptive and inferential statistical analyses with SPSS. The results demonstrated that SAC positively contributed on students' learning interest. Specifically, 85.71% of students reported feeling that the classroom atmosphere became more enjoyable, and 85.71% were focused and attentive during integrated science studies when using SAC as the learning media. Moreover, 85.71% of students expressed satisfaction and comfort while learning integrated science with SAC. Additionally, 86.9% of students exhibited good participation in the learning process. Based on the data, it can be concluded that the utilization of mobile learning using SAC has a positive effect on students' learning interest in integrated science.Keywords: Android-based learning, Integrated science, Mobile learning, Smart apps creator (SAC), Student interest